Analisis Yuridis Keterangan Saksi Testimonium De Auditu dalam Surat Pernyataan Sporadik Penguasaan Tanah Perspektif Kepastian Hukum - I Gede Ngurah Budi Eka Prayusa; Yogi Yasa Wedha (Jurnal Hukum Mahasiswa, 2026)
Land registration through the proof of old rights may be conducted based on physical possession of land for twenty years or more, as evidenced by a sporadic statement letter and supported by the testimony of at least two witnesses. However, this provision allows the use of testimonium de auditu testimony, namely statements based on hearsay that cannot be materially verified. In practice, the assessment of proof of old rights as regulated under Article 24 paragraph (1) of Government Regulation No. 24 of 1997 contains the phrases “degree of truth” and “deemed sufficient” without clear parameters, thereby creating legal uncertainty. This normative juridical research employs the theory of legal certainty and the theory of evidence to analyze two main issues: the regulation of land registration in Indonesia and the evidentiary strength of testimonium de auditu testimony. The findings indicate that testimonium de auditu testimony does not meet the criteria of a valid witness and fails to provide legal certainty, while the ambiguity of the norm necessitates further regulatory clarification